2016
DOI: 10.1111/myc.12542
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis in patients with nail psoriasis: a point to point discussion

Abstract: Onychomycosis is the most common nail disease and affects large parts of the population. Psoriasis is a frequently encountered skin disorder with nail involvement being found in up to 80% of the patients at some time of the course of the disease. It has been postulated that onychomycosis occurs more frequently in patients with nail psoriasis, but the results of studies in the literature are controversial. Moreover, onychomycosis could exacerbate psoriasis through Koebner phenomenon and the treatment of psorias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 46 publications
1
48
1
4
Order By: Relevance
“…Few studies, also examining only nail psoriasis patients found a substantially higher prevalence of onychomycosis among them; it is possible that the inclusion of patients currently being or having recently been treated with immunosuppressive agents can justify the noted difference . The majority of studies examining psoriasis patients with as well as without psoriatic nail lesions have reported a smaller prevalence of onychomycosis than the one found in our study . This discrepancy is possibly attributed to the fact that psoriasis patients with clinically healthy nails seem to be less susceptible to dermatophyte infections of the nail than the general population.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Few studies, also examining only nail psoriasis patients found a substantially higher prevalence of onychomycosis among them; it is possible that the inclusion of patients currently being or having recently been treated with immunosuppressive agents can justify the noted difference . The majority of studies examining psoriasis patients with as well as without psoriatic nail lesions have reported a smaller prevalence of onychomycosis than the one found in our study . This discrepancy is possibly attributed to the fact that psoriasis patients with clinically healthy nails seem to be less susceptible to dermatophyte infections of the nail than the general population.…”
Section: Discussioncontrasting
confidence: 85%
“…Although no significant difference was observed between the 2 groups regarding the growth of T. mentagrophytes , C. albicans grew significantly more in psoriatic keratin. The faster growth of psoriatic nails, the presence of anti‐dermatophyte‐acting peptides and the altered structure of nails with psoriatic lesions might be responsible for this phenomenon …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful treatment may sometimes eliminate the fungal elements and achieve a mycological cure, but not a clinical cure [4]. In psoriatic patients, several nails could be involved or one nail might have psoriasis alone or psoriasis combined with onychomycosis, while the adjacent nail might be healthy but infected with fungus [15]. …”
Section: Bearing In Mind Inflammatory Skin Diseasesmentioning
confidence: 99%